2014
DOI: 10.1371/journal.pone.0096007
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns and Subcellular Localization of Carbonic Anhydrases Are Developmentally Regulated during Tooth Formation

Abstract: Carbonic anhydrases (CAs) play fundamental roles in several physiological events, and emerging evidence points at their involvement in an array of disorders, including cancer. The expression of CAs in the different cells of teeth is unknown, let alone their expression patterns during odontogenesis. As a first step towards understanding the role of CAs during odontogenesis, we used immunohistochemistry, histochemistry and in situ hybridization to reveal hitherto unknown dynamic distribution patterns of eight CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 84 publications
3
30
0
Order By: Relevance
“…The data are also in accordance with previous studies (Amasheh et al, 2009;Colegio, Van Itallie, McCrea, Rahner, & Anderson, 2002;Lal-Nag & Morin, 2009) showing the expression of Cldn1, Cldn4, and Cldn8 in maturation-stage ameloblasts (Hata, Kawamoto, Kawai, & Yamamoto, 2010;Inai, Sengoku, Hirose, Iida, & Shibata, 2008). As previous studies show, ion transporters necessary for intracellular and extracellular pH regulation such as Slc9a1/Nhe1, Slc4a2/Ae2, Slc4a4/Nbce1, Slc26a4/pendrin, and CFTR (Bronckers et al, 2011;Jalali et al, 2014; and the cytoplasmic Car2 isoform of carbonic anhydrases (Lacruz, Smith, Moffatt, et al, 2012;Reibring et al, 2014) are expressed by ameloblasts. We identified all of them in HAT-7 cells suggesting that this cell line is suitable as an experimental model for studying ameloblast acid/base transport.…”
Section: The Hat-7 Cell Model To Functionally Study Ph Regulation Bsupporting
confidence: 92%
See 1 more Smart Citation
“…The data are also in accordance with previous studies (Amasheh et al, 2009;Colegio, Van Itallie, McCrea, Rahner, & Anderson, 2002;Lal-Nag & Morin, 2009) showing the expression of Cldn1, Cldn4, and Cldn8 in maturation-stage ameloblasts (Hata, Kawamoto, Kawai, & Yamamoto, 2010;Inai, Sengoku, Hirose, Iida, & Shibata, 2008). As previous studies show, ion transporters necessary for intracellular and extracellular pH regulation such as Slc9a1/Nhe1, Slc4a2/Ae2, Slc4a4/Nbce1, Slc26a4/pendrin, and CFTR (Bronckers et al, 2011;Jalali et al, 2014; and the cytoplasmic Car2 isoform of carbonic anhydrases (Lacruz, Smith, Moffatt, et al, 2012;Reibring et al, 2014) are expressed by ameloblasts. We identified all of them in HAT-7 cells suggesting that this cell line is suitable as an experimental model for studying ameloblast acid/base transport.…”
Section: The Hat-7 Cell Model To Functionally Study Ph Regulation Bsupporting
confidence: 92%
“…We also found that the application of the membrane permeable carbonic anhydrase inhibitor acetazolamide partially inhibited the basolateral base flux in HAT‐7 cells suggesting that this mechanism is present, and coupled to H + extrusion via a basolateral Na + ‐H + exchanger such as NHE1 (Bori et al., ). Among the large number of different isoenzymes in the carbonic anhydrase gene family, the dominant isoform in ameloblasts is Car2 (Lacruz, Smith, Moffatt, et al., ; Reibring et al., ), the isoform that we found to be expressed in HAT‐7 cells (Bori et al., ).…”
Section: The Hat‐7 Cell Model To Functionally Study Ph Regulation By mentioning
confidence: 74%
“…Therefore, it is possible that other members of the CA family can serve as functional NP markers. Noteworthy, expression of CAII, CAIII, and CAVI has been shown in embryonic mouse notochord and/or NP [105]. In addition, robust expression of CAIII transcripts in early notochordal and NP has been shown [106].…”
Section: Markers Specific To Cell Function In the Np Microenvironmentmentioning
confidence: 99%
“…In some metazoan groups, α-CAs have been described as a calcium-dissolving enzyme, as in the bones of vertebrates and the spicules of calcareous sponges such as Sycon raphanus [45]. Recently, eight CAs in murine, produced by ameloblasts, were identified to be involved in biomineralization during teeth development [46]. In corals, α-CA isoforms interact in the carbon cycle of the endosymbiotic zooxanthellae playing an indirect role in skeletal formation [19].…”
Section: The α-Carbonic Anhydrases Familymentioning
confidence: 99%